Pemberdayaan Anggota dan Pengurus Koperasi Perempuan Wirausaha Mandiri Kota Jambi melalui Pelatihan Koperasi Berbasis Digital Menuju Koperasi Modern - Sumirah, Sumirah; Jevi Saputra (Yayasan Literasi Sains Indonesia, 2025)
This community service aimed to empower members and managers of the Women's Independent Empowerment Entrepreneurial Cooperative in Jambi City through training on digital cooperatives. The study employed a Participatory Action Research (PAR) method, actively involving participants in the empowerment process and educating them on managing digital cooperatives. Findings revealed that women's involvement in cooperative management and membership is vital for the organization's sustainability. Members of cooperatives supported by the Jambi city government responded positively to digitalization and actively participated in various training and cooperative activities. However, the Jambi City Independent Empowerment Entrepreneurial Cooperative still faces challenges in gaining socialization regarding digitalization in its management system. To adapt to the digital era, cooperatives must be prepared to change and enhance their technological skills. The results suggest that empowerment should be implemented sustainably, leading to a digital-based empowerment model. The study concludes that women have an important role in cooperatives, and digitalization is necessary to improve the capabilities of managers and members. Members of the cooperative responded positively to digitalization, and this policy provides benefits for the cooperative to compete and expand its business reach. The Jambi City Independent Empowerment Entrepreneurial Cooperative still needs to increase socialization of digitalization in its management system. Cooperatives must be prepared to adapt and develop technological capabilities in the digital era.